Aristotle's theory of substance : the Categories and Metaphysics Zeta - Wedin, Michael V. (Michael Vernon), 1943- (Oxford Aristotle studies., 2000)
Aristotle's views on the fundamental nature of reality are usually taken to be inconsistent. Two sources for these views are 'Categories' and the central books of 'Metaphysics'. This text argues that he is engaged in different projects in these books.